High Tg, melt processable copolyimides based on isomeric 3, 3′ and 4, 4′-hydroquinone diphthalic anhydride (HQDPA). (31st January 2018) - Sidra, Lala Rukh; Chen, Guofei; Mushtaq, Nafeesa; Xu, Lubo; Chen, Xiaoqi; Li, Yantao; Fang, Xingzhong
Abstract: To extend the upper operating temperature range of melt processable PIs, two series of end-capped copolyimides based on hydroquinone diphthalic anhydride (HQDPA) isomers were designed by varying the contents of appropriate diamines. Thus, copolyimides PI-(0a∼20a) based on 3, 3′-HQDPA were prepared by varying the ratio of rigid 2-(4-aminophenyl)-5-aminobenzimidazole (BIA) and flexible 4, 4′-oxydianiline (ODA). The resulting copolyimides demonstrated good properties, such as excellent solubility, high T g ranging from 328 to 354 °C as determined by dynamic mechanical analyzer (DMA), besides, exhibited good thermal stability based on 5% weight loss temperature ( T 5% ) of 502–514 °C and low melt viscosity in the range of 291–935 Pa·s. Most importantly, PI-20a showed a good combination of low melt viscosity simultaneously with significantly high T g (328 °C). Furthermore, this system was modified by copolymerization with different feed ratio of 4, 4′-HQDPA isomer and produced another series PI-(20a∼20e), that exhibited high T g in the range of 315–330 °C with T 5% of 502–543 °C and minimum complex viscosity in the range of 291–479 Pa·s. All PIs form tough and flexible films that have remarkable tensile strength and moduli in the range of 93–116 MPa and 3.7–4.7 GPa, respectively. Graphical abstract: Highlights: The effect of mixture of 3, 3′ and 4, 4′-HQDPA isomers on properties is explored. The feed ratio of monomers played a critical role on rheological properties and T g . Polyimides showed high T g with upper use temperature >250 °C and good processability. PI-20a showed best results and also exhibited high upper working temperature.